ADVANCED NANOCARRIERS FOR OCULAR DRUG DELIVERY: STRATEGIES TO OVERCOME OCULAR BARRIERS - DIVYA; MAZUMDER, RUPA; RANI, ANJNA; MISHRA, RAKHI (International Journal of Applied Pharmaceutics, 2025)
Ocular drug delivery is confronted with significant challenges because of the eye's specific anatomy and physiological barriers, including the blood-retinal and corneal epithelium. Traditional dose formulations often experienced rapid precorneal clearance and low absorption. Recent advances in nanotechnology, such as liposomes, cubosomes, glycerosomes, nano wafers, microneedles, vectors for gene therapy, olaminosomes, bilosomes, and exosomes, offer promising alternatives to bypass these limitations. These techniques facilitate longer ocular retention, controlled release, targeted distribution, enhanced drug solubility, and improved patient compliance. For instance, glycerosomes and nanoliposomes enhance permeability and biocompatibility; nanogels and cubosomes have structural advantages for drug stabilization and sensitivity; microneedles offer a minimally invasive approach to achieve epithelial barriers; exosomes enable targeted bioactivity and intracellular delivery; and olaminosomes, which are made of lipid-based vesicles and oleylamine, offer great entrapment efficiency and corneal adherence. In contrast, bilosomes, which incorporate bile salts, improve corneal permeability. The present work provides comprehensive insights into nanocarrier approaches for improving ocular bioavailability, along with related patents and clinical trials in this field.